Mental Disorder During Adolescence: Evidence of Arrested Personality Development. (May 2020) - Ormel, Johan; Oerlemans, Anoek M.; Raven, Dennis; Oldehinkel, Albertine J.; Laceulle, Odilia M.
The experience of a mental disorder may affect the development of personality in multiple ways, but empirical evidence regarding psychopathology effects on personality development that persist after remission of the disorder is limited and inconsistent. In the longitudinal cohort TRacking Adolescents' Individual Lives Survey (TRAILS), mental disorders during adolescence were assessed using the Composite International Diagnostic Interview and parent-reported effortful control, fearfulness, and frustration at age 11 and age 19 through the Early Adolescent Temperament Questionnaire. We found that adolescent mental disorders had small effects on personality change. Internalizing disorders predicted increases of fearfulness and frustration but hardly affected effortful control; externalizing disorders were unrelated to frustration and fearfulness but predicted a decrease of effortful control. Whereas fearfulness and frustration partially caught up after disorder remission, virtually all delay in effortful control was still present 2.9 years later, suggesting scarring effects.